Biochemistry: The molecular basis of life - McKee, Trudy; McKee, James R; McKee, Trudy (New York, Oxford University Press, 2017)
The Molecular Basis of Life is an intermediate, one-semester text written for students on degree pathways in Chemistry, Biology, and other Health and Life Sciences. Designed for students who need a solid introduction to biochemistry, but are not specializing in the subject, the text focuses on essential biochemical principles that underpin the modern life sciences, and offers the most balanced coverage of chemistry and biology of any text on the market. The text equips students with a complete view of the living state, emphasizes problem solving, and applies biochemical principles to the fields of Health, Agriculture, Engineering, and Forensics, to show students the relevance of their learning. McKee and McKee is respected for its balance of biology and chemistry, consistently placing biochemical principles into the context of the physiology of the cell and biomedical applications.
Appendix A1-A46p.; Glossary G1-G17p.; Index I1-I34p.
Keywords: Carbohydrates; Enzymes; Nucleic acids; Chemistry